(untitled) (Global Journal of Human-Social Science, 2019)
This study examines the impact of China’s currency swap agreements with Nigeria on U.S. dollar’s exchange rate with naira between 1999 and 2017 using Robust Least Squares (ROBUSTLS) technique. The results of the finding reveal that China’s currency swap agreement with Nigeria tends to have a reasonable impact on the exchange rate (value) of U.S. dollar. Since the existing works on bilateral currencies swap agreements between China and other countries (excluding Nigeria) reveal that the U.S. dollar dominates all other international currencies in trade settlement and with the aim of bypassing the U.S. dollar in international trades, this study therefore provides fresh empirical evidence on the impact of China’s currency swap agreements with Nigeria on the U.S. dollar’s exchange rate and concludes that China’s currency swap agreement with Nigeria will raise the exchange rate of naira and lower the value of the U.S. dollar with respect to Nigerian naira.